2014
DOI: 10.1016/j.bone.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

The effect of conditional inactivation of beta 1 integrins using twist 2 Cre, Osterix Cre and osteocalcin Cre lines on skeletal phenotype

Abstract: Skeletal development and growth are complex processes regulated by multiple microenvironmental cues, including integrin-ECM interactions. The β1 sub-family of integrins is the largest integrin sub-family and constitutes the main integrin binding partners of collagen I, the major ECM component of bone. As complete β1 integrin integrin knockout results in embryonic lethality, studies of β1 integrin function in vivo rely on tissue-specific gene deletions. While multiple in vitro studies indicate that β1 integrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 61 publications
2
35
0
Order By: Relevance
“…While the Osx-Cre transgene has been reported to cause delayed or defective skeletal and craniofacial mineralization resulting from Osterix loss-of-function [35-37], studies including analysis of molar teeth have not identified similar dental defects [30, 38, 39]. To rule out dental alterations from the Osx-Cre transgene, several control genotypes were analyzed (Supplementary Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…While the Osx-Cre transgene has been reported to cause delayed or defective skeletal and craniofacial mineralization resulting from Osterix loss-of-function [35-37], studies including analysis of molar teeth have not identified similar dental defects [30, 38, 39]. To rule out dental alterations from the Osx-Cre transgene, several control genotypes were analyzed (Supplementary Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Third, activation of integrin α5β1 or the extracellular matrix (ECM)-integrin α5β1 interactions via RGD binding have been linked to the control of osteoblastogenesis through activation of TRPV4 ion channels and FAK/RhoA-ROCK/ERK [40–42, 158160]. Fourth, integrin α5β1 affects bone formation in osteoblasts and osteocytes in vivo [161164]. …”
Section: Role Of Other Mechanosensors In Bonementioning
confidence: 99%
“…The role of ILK has been less profoundly characterized, and especially, information on its functioning early in the osteoblast lineage is lacking. Yet previous transgenic expression of a dominant‐negative β1 integrin subunit or conditional inactivation of β1 integrin, FAK, or ILK in mature osteoblasts was without discernible effects or only mildly or transiently affected the skeleton in basal conditions, whereas recent studies in which β1 integrin or FAK were targeted in osteogenic progenitors revealed important functions for these molecules in the control of bone formation.…”
Section: Introductionmentioning
confidence: 98%